Sources of Influence on Beliefs About Information Technology Use: An Empirical Study of Knowledge Workers1 - Lewis, William; Agarwal, Ritu; Sambamurthy, V. (MIS Quarterly, 2003)
Individual beliefs about technology use have been shown to have a profound impact on subsequent behaviors toward information technology (IT). This research note builds upon and extends prior research examining factors that influence key individual beliefs about technology use. It is argued that individuals form beliefs about their use of information technologies within a broad milieu of influences emanating from the individual, institutional, and social contexts in which they interact with IT. We examine the simultaneous effects of these three sets of influences on beliefs about usefulness and ease of use in the context of a contemporary technology targeted at autonomous knowledge workers. Our findings suggest that beliefs about technology use can be influenced by top management commitment to new technology and the individual factors of personal innovativeness and self-efficacy. Surprisingly, social influences from multiple sources exhibited no significant effects. Theoretical and practical implications are offered.